Sliding Modes Control for Heat Transfer in Geodesic Domes - Frank Florez; Pedro Fernández de Cordoba; John Taborda; Miguel Polo; Juan Carlos Castro-Palacio; María Jezabel Pérez-Quiles (Mathematics, 2020)
The analysis and modeling of unconventional thermal zones is a first step for the inclusion of low-cost spaces and for the assessment of the environmental impact among areas of human use in warm climates. In this paper, the heat transfer in a geodesic dome located at the University of Magdalena (Colombia) is modeled and simulated. The simulator is calibrated against experimental measurements and used to study the effect of different loads which are regulated by a controller in sliding modes explicitly designed for this case. The closed-loop system is used together with ASHRAE Standard 55 to characterize comfort conditions within the dome and the effect on the overall thermal sensation with increasing the number of occupants.